Ethnography of Communication Analysis in Luca Movie Dialogue - Rekiyan Nurfridayanti; Ansor Putra; Rahmawati Azi (ELITE: Journal of English Language and Literature, 2022)
This study aimed to analyze the ethnography of communication, ethnographic components, and how to explain it using the theory proposed by Dell Hymes. This study discussed the settings/scenes, participants, ends, action sequences, keys, elements, instrumentalities, norms, and genres of the communication summarized in the acronym SPEAKING model in Luca movie dialogue. To make it easy for readers to understand, all the categories mentioned were grouped according to the analysis under study. This ethnographic study focuses on communicative competence in society related to its culture. The researcher used qualitative descriptive research methods to describe and interpret objects according to the current situation. The descriptive method is applied in an integrated manner because in analyzing the data, it is presented in a clearer explanation. The researcher then analyzed the dialogue in the Luca movie by using a descriptive qualitative research method. The finding in this movie is a conversational genre is found which generally becomes the human daily conversation. This movie uses language that is easy for the readers to understand because it uses everyday language whose words can be easily understood. The data found in this study include 141 dialogues based on the variety of topics discussed by the participants. In conclusion, the part of the discussion is that the researcher found some data that included several category elements from the ethnography of communication and then made conclusions from the use of ethnography of communication elements in the research findings section.